THE DEVELOPMENT OF ENGLISH TODDLER BOOK BASED MORAL VALUE - Harahap, Amelia (Universitas Muhammadiyah Muara Bungo, 2023)
This research was about the development of english toddler book based moral value. The purpose of this research is to see the development of English and moral value toddler through the application of English book based moral value. The method would used in this research is research and development. According to (Thiagarajan, 1974) states that development 4D model is a system approach model where compiled and based on previous models and based on actual field experience in designing, developing, evaluating, and disseminating teacher training materials in education special. Data collecting technique in this research is used questionnaires and observation sheets. The results of this research indicate that the English book based moral value in this development research are valid for use with good quality media. the result of content validation by content expert is 75.5% in valid category, the result of media validation by media expert is 92.5% in very valid category, the result of teacher perspective is 97% and the final result of observation is 94.4%.